SCLC Treatment in the Immuno-Oncology Era: Current Evidence and Unmet Needs - Belluomini, Lorenzo; Calvetti, Lorenzo; Inno, Alessandro; Pasello, Giulia; Roca, Elisa; Vattemi, Emanuela; Veccia, Antonello; Menis, Jessica; Pilotto, Sara (Frontiers in Oncology, 2022)
Small cell lung cancer (SCLC) represents about 13-15% of all lung cancers. It has a particularly unfavorable prognosis and in about 70% of cases occurs in the advanced stage (extended disease). Three phase III studies tested the combination of immunotherapy (atezolizumab, durvalumab with or without tremelimumab, and pembrolizumab) with double platinum chemotherapy, with practice-changing results. However, although the high tumor mutational load and the chronic pro-inflammatory state induced by prolonged exposure to cigarette smoke, the benefit observed with immunotherapy is very modest and most patients experience disease recurrence. Unfortunately, biological, clinical, or molecular factors that can predict this risk have not yet been identified. In the light of the results achieved in the last two years, and the remarkable improvement in the prognosis of patients with SCLC, we have moved from a” disease “orphan” of therapeutic innovation to an increasingly subject of study, where promising new treatment combinations will become part of the clinical practice. It goes without saying that in the coming years we will witness a significant upheaval of the current therapeutic algorithm, which will gradually be enriched with new treatment strategies, and molecular targets. Following the recent therapeutic innovations, we have reviewed the available literature data about SCLC management, with a focus on current unmet needs and potential predictive factors. In detail, the role of radiotherapy, fragile populations, such as elderly or low-performance status patients (ECOG PS 2), usually excluded from randomized studies, predictive factors of response useful to optimize and guide therapeutic choices, as well as new molecular targets and future combinations have been explored and revised.